Determinants of measles second dose vaccination dropout among children aged 18–24 months in Ejere woreda, central Ethiopia; unmatched case-control study - Nurgi, Kitessa; Ahmed, Seifadin; Ganfure, Gemechu; Bekele, Gemechu Gelan (Frontiers in Pediatrics, 2024)
Background: Measles continues to pose a significant public health challenge, especially in lowand middle-income countries. Despite the implementation of national vaccination programs, measles outbreaks persist in some parts of Ethiopia, and the determinants of dropout from the second measles vaccine dose are not well understood. Hence, this study aimed to assess determinants of measles second dose vaccination dropout among children aged 18-24 months in Ejere woreda, central Ethiopia.Methods: A community-based unmatched case-control design was conducted in the Ejere Woreda of the Oromia regional state in Ethiopia between February 14 and April 6, 2023. Data were collected using a pre-tested structured questionnaire. The collected data were coded and entered into Epi-data version 3.1 and then transported to SPSS version 27 for statistical analysis.Descriptive analysis like frequency, mean, and percentage was calculated. Binary and multivariable logistic regression analysis was done. Finally, variables with a p-value <0.05 were considered statistically significant.Result: A total of 446 mothers/caregivers, comprising 110 cases and 336 controls, participated in this study, making the response rate 97.8%. Lack of a reminder for the measles vaccine during postnatal care (PNC) (AOR = 5.19; 95% CI: 2.34, 7.83), having ≤ 2 antenatal care (ANC) contacts (AOR = 4.95; 95% CI: 2.86, 9.24), long waiting times during previous vaccination (AOR = 2.78; 95% CI: 1.19, 4.38), children of mothers/caregivers without formal education (AOR = 6.46; 95% CI: 2.81, 11.71), mothers/caregivers of children who were unaware of the importance of the second dose of measles (AOR = 8.37; 95% CI: 4.22, 15.08), and mothers/caregivers whose children did not receive at least two doses of vitamin A (AOR = 4.05; 95% CI: 2.15, 8.11) were significant determinants of measles second dose vaccination dropout.health facilities for other vaccines can significantly improve the uptake of the second dose of the measles vaccine. These strategies not only enhance overall vaccination coverage but also mitigate the risk of measles outbreaks in the community.